(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
In the article, the pragmatic features of expression of incomplete sentences in the two languages are almost the same, and the pragmatic obstacle caused by irregular use or pronunciation is observed in both languages with the help of examples.